Slalom E-Book - Endicott, W. T. (2009)
A quarter century ago, the author wrote 3 books on whitewater slalom, "The River Masters" (1977), "To Win The Worlds" (1979), and "The Ultimate Run" (1981). Ever since then, he has been meeting racers from around the world who tell me they got into the sport because of these books, or learned about serious training from them. But now they are out of date and even if they weren`t, the Internet has opened up a whole new way of transmitting information more efficiently. So, the purpose of this document is to combine the information from those books in one place, modernize it, introduce new ways to explain it, and place the whole thing on-line, free of charge, as an ICF project. The author thanks ICF Slalom Racing Committee Chairman, Jean Michel Prono, for making this possible. It is the vision of the author the project will make it easier for new athletes to learn about canoe slalom and reach a reasonably high level of ability. Besides athletes from countries that already do slalom racing, he is hoping athletes in new countries in, say, Africa, South America and Asia, will now be able to join the canou slalom family.